46. MOLECULAR DYNAMICS OF ARTEMISININ RESISTANCE IN PLASMODIUM FALCIPARUM IN SEVERAL PROVINCES OF CENTRAL HIGHGHLANDS 2016-2021 (Vietnam Journal of Community Medicine, 2024)
Objectives: Determining the prevalence of K13 gene mutations, a marker of artemisinin resistance, from 2016 to 2021 in the Central Highlands is essential to better understand the status of malaria resistance in the region. Methods: Total DNA was extracted and used in Nested-PCR techniques to identify four species of malaria parasites; Sanger sequencing was performed to identify K13 gene mutations. Results: A total of 539 blood samples were collected from 2019 to 2021, along with 304 retrospective samples from 2016 to 2018 in Gia Lai, Đăk Lắk, and Đăk Nông. The prevalence of the C580Y mutation increased over the periods: in Gia Lai, it was 22.91% (2016-2017), 69.77% (2018-2019), and 98.18% (2020-2021); in Đăk Lắk, the rates were 44.78%, 87.95%, and 86.07%; and in Đăk Nông, they were 50%, 79.55%, and 100%. The K13 gene mutations identified as resistant according to WHO in Gia Lai were ¾ types (C580Y, P553L, I543T); in Đăk Lắk, 2/4 types (C580Y, R539T); and in Đăk Nông, 2/3 types (C580Y, R539T, and the new mutation F446I). Conclusion: The majority of K13 mutations in Gia Lai, Đăk Lắk, and Đăk Nông are identified as artemisinin-resistant mutations according to WHO, with C580Y being the most significant. The increasing rates of these mutations over time may correlate with the clinical drug resistance status in the region.
Keywords: Plasmodium falciparum; artemisinin resistance; molecular maker